Nutraceutical value of tropical tuber crops - Jyothi, A N; Pradeepika, C (Indian Horticulture, 2025)
Tropical root and tuber crops viz., cassava, sweet potato, yams, taro, tannia, elephant foot yam, and minor species like arrowroots are vital for food security, nutrition, and income in developing countries. Rich in carbohydrates, vitamins, minerals, and bioactive compounds, they offer both dietary energy and health promoting benefits. Orange and purple-fleshed varieties provide β-caroteneand anthocyanins that help combat vitamin A deficiency and oxidative stress. Phytochemicals from yams, aroids, and minor tubers exhibit antioxidant, anti-inflammatory, and hypoglycemic activities. The growing recognition of these nutritional and functional benefits highlights the potential of tropical tuber crops in combating malnutrition and lifestyle-related diseases while fostering valueaddition and livelihood security.